2015
DOI: 10.1186/s12877-015-0086-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a multicomponent intervention to prevent physical restraints in nursing home residents (IMPRINT): study protocol for a cluster-randomised controlled trial

Abstract: BackgroundPhysical restraints such as bedrails and belts are regularly applied in German nursing homes despite clear evidence showing their lack of effectiveness and safety. In a cluster-randomised controlled trial, the efficacy and safety of a guideline-based multicomponent intervention programme has been proven. The present study aims to evaluate the effectiveness of two different versions of the original intervention in nursing home residents in four different regions throughout Germany.Methods/DesignThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Our observations that restraints were used for the most vulnerable and disabled persons with poor ADL functioning are supported by others (Karlsson et al ., ; Hamers and Huizing, ; Saarnio et al ., ). It can be discussed, how much this practice is a matter of nursing traditions and routines, because nurses have a decisive role in the application of physical restraints for fall prevention (Evans et al ., ; Möhler and Meyer, ) and to control NPS (Hamers and Huizing, ; Meyer et al ., ; Abraham et al ., ). No typical organizational variables are associated with restraint use (Hofmann et al ., ), but routines, ignorance of alternatives and even requests by the family may increase their use (Gastmans and Milisen, ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our observations that restraints were used for the most vulnerable and disabled persons with poor ADL functioning are supported by others (Karlsson et al ., ; Hamers and Huizing, ; Saarnio et al ., ). It can be discussed, how much this practice is a matter of nursing traditions and routines, because nurses have a decisive role in the application of physical restraints for fall prevention (Evans et al ., ; Möhler and Meyer, ) and to control NPS (Hamers and Huizing, ; Meyer et al ., ; Abraham et al ., ). No typical organizational variables are associated with restraint use (Hofmann et al ., ), but routines, ignorance of alternatives and even requests by the family may increase their use (Gastmans and Milisen, ).…”
Section: Discussionmentioning
confidence: 97%
“…The use of physical restraints has also been related to direct injuries through fatal entrapments as well as to reduced psychological well‐being (Evans et al ., ; Castle and Engberg, ; Scherder et al ., ). Moreover, restraints apparently do not reduce falls or fall‐related injuries, nor do they control NPS (Evans et al ., ; Köpke et al ., ; Möhler et al ., ; Abraham et al ., ), but in opposite, increase further risks for restrained persons (Hofmann and Hahn, ). The use of restraints may impact negatively on a person's dignity, autonomy and integrity, and cause a traumatic experience (Gallinagh et al ., , Gastmans and Milisen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The applied facilitation approach is a proven strategy for implementing interventions in nursing homes and for supporting changes in the daily nursing routine [40][41][42][43]. A successful implementation of knowledge into practice depends on the quality and type of the evidence, existing speci c nursing home characteristics and the modalities of facilitation [21].…”
Section: Discussionmentioning
confidence: 99%
“…This was confirmed by our own study, which revealed that the implementation of the German evidence-based guideline in nursing homes was effective in reducing PR without increasing adverse effects like falls or fall-related injuries [ 5 ]. Currently, the effectiveness and safety of a large-scale implementation of the updated German evidence-based guideline is being investigated in a pragmatic trial [ 28 ]. This indicated that the PR use can be reduced by offering recommendations for nursing staff, based on the best available evidence.…”
Section: Discussionmentioning
confidence: 99%